PENGARUH PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR SOSIOLOGI SMA ISLAM BAWARI PONTIANAK - Handayani, Handayani; Zakso, Amrazi; Alhidayah, Riama (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research was to know the effect of application Discovery Learning to the student’s results study on science subject in class XI IIS SMA Islam Bawari Pontianak. The researcher used quantitative method which descriptive statistic. The sample of this research was 49 students with proportional random sampling. In collecting the data, the researcher used questionnaire for the application of Discovery learning method and the score of student’s daily exam for the student’s results study. The statistical test used in this study was with a simple linear regression analysis. This research shows that the application of Discovery Learning in class XI IIS SMA Islam Bawari Pontianak had the average height of 59.55 whereas the result of studying on sociology subjects was 66.76. The results show that the students were failed. The application of discovery learning shows that there was not significant to the student’s results study and the score was 2.8%. It was means the used of learning model was not gave effect to the student’s results study on sociology subject. It was thought that the effect was from other variables were left unstudied.Keywords: Discovery learning, Learning model, results of study